Glycaemic control in type 2 diabetic patients with chronic kidney disease: the impacts on enzymatic antioxidants and soluble RAGE - Wong, Foo Nian; Chua, Kek Heng; Tan, Jin Ai Mary Anne; Wong, Chew Ming; Kuppusamy, Umah Rani (PeerJ, 2018)
Background. Chronic kidney disease (CKD) is characterised by long-term kidney damage and renal function decline. Diabetic CKD is the principal subtype of kidney disease in Malaysia and is associated with oxidative stress which plays an important role in development and progression of the disease. Glycaemic control slows down the progression of diabetic complications, including diabetic CKD. However, the implication of glycaemic control on enzymatic antioxidants and solubleRAGE(sRAGE) in CKD patients remains elusive. The aim of this study was to investigate the effect of glycaemic control on the levels or activities of glutathione peroxidase (GPx), superoxide dismutase (SOD) and sRAGE in CKD patients. Methods. A total of 150 CKD patients and 64 non-CKD patients were enrolled. The type 2 diabetic patients in the recruited study participants were categorised based on their glycaemic control; poor glycaemic control (GC) with haemoglobin A1c (HbA1c) < 7% and good GC with HbA1c ≤ 7%. The levels or activities of GPx, SOD and sRAGE in plasma were measured. These biochemical parameters were analysed using Mann-Whitney U test and two-way analysis of variance (ANOVA). Results. The activities of GPx and SOD as well as plasma level of sRAGE were not significantly different among the CKD patients with varying glycaemic control status. Irrespective of diabetes status and glycaemic control status, CKD patients also exhibited lower plasma SOD activities compared with non-CKD patients. Among the non-CKD patients, SOD activities were significantly higher in diabetic patients with good GC than diabetic patients with poor GC. Two-way ANOVA revealed that both CKD status and glycaemic control had an interaction effect on SOD activities in diabetic subjects with and without CKD. Follow-up analysis showed that SOD activities were significantly higher in non-CKD patients with good GC. There were no overall significant differences in GPx activities among the study participants. Furthermore, plasma sRAGE levels were higher in diabetic patients with CKD than those without CKD, regardless of glycaemic control status. There were no interaction effects between CKD status and glycaemic control status on GPx and sRAGE. Instead, CKD status showed significant main effects on these parameters, indicating significant differences between diabetic subjects with CKD and diabetic subjects without CKD. Conclusion. Glycaemic control did not quantitatively alter GPx, SOD and sRAGE in diabetic CKD patients. Despite the advantages of good glycaemic control, a well-controlled diabetes in CKD did not modulate the activities of enzymatic antiox- idants and sRAGE levels, therefore may not be the primary mechanism to handle oxidative stress.